Characterization of recombinant L-ribose isomerase acquired from Cryobacterium sp. N21 with potential application in L-ribulose production. (October 2020) - Mahmood, Shahid; Iqbal, Muhammad Waheed; Riaz, Tahreem; Zhang, Wenli; Mu, Wanmeng
Graphical abstract: Highlights: L-Ribulose producing l -ribose isomerase was characterized from Cryobacterium sp. N21. CrL-RIse showed maximum activity at 35 °C and pH 9.0 in glycine-NaOH (50 mmol) buffer. CrL-RIse showed highest specific activity (54.96 U mg −1 ) with l -ribose as substrate as compared to other l -RIs. The recombinant CrL-RIse produced 31 % l -ribulose as the sole product from l -ribose. Abstract: l -Ribose isomerase (l RI) is an enzyme that can catalyze the reversible isomerization between l -ribose and l -ribulose. It can also perform the conversion between many aldoses into their corresponding ketoses. l -RI was produced from Cryobacterium sp. N21 (CrL-RIse), and l -ribose was utilized as a substrate. The recombinant l -RI gene was cloned and overexpressed from Cryobacterium sp. N21. The purification of CrL-RIse was performed by metal-affinity chromatography. The enzyme displayed a corresponding band with an approximate size of 35 kDa on the SDS-PAGE analysis. The protein for this gene contains 266 amino acids with an expected molecular weight (M w ) of 29.6 kDa. The measured M w of CrL-RIse calculated by HPLC was 125 kDa. CrL-RIse was extremely active in glycine buffer at 35 °C, pH 9.0, showing a specific activity of 54.96 U mg −1 . CrL-RIse displayed no major increase in activity with metal ions, excluding Mn 2+ . The estimated Km, Kca t, Kcat /Km and Vmax values of CrL-RIse were 37.8 mM, 10, 416 min −1, 275.43 min −1  mM −1, and 250 U mg −1, respectively. The rate of l -ribulose production was 31 % (6.24, 12.11, and 20.89 g L −1 ) at equilibrium by utilizing 20, 40, and 70 g L −1 of the substrate, respectively. The results indicated that CrL-RIse has the capability to manufacture l -ribulose from l -ribose.